Electromagnetic Electron Cyclotron Instability in the Solar Wind. Issue 1 (11th January 2018) - Lazar, M.; Yoon, P. H.; López, R. A.; Moya, P. S.
Abstract: The abundant reports on the existence of electromagnetic high‐frequency fluctuations in space plasmas have increased the expectations that theoretical modeling may help understand their origins and implications (e.g., kinetic instabilities and dissipation). This paper presents an extended quasi‐linear approach of the electromagnetic electron cyclotron instability in conditions typical for the solar wind, where the anisotropic electrons ( T ⊥ > T ∥ ) exhibit a dual distribution combining a bi‐Maxwellian core and bi‐Kappa halo. Involving both the core and halo populations, the instability is triggered by the cumulative effects of these components, mainly depending of their anisotropies. The instability is not very sensitive to the shape of halo distribution function conditioned in this case by the power index κ . This result seems to be a direct consequence of the low density of electron halo, which is assumed more dilute than the core component in conformity with the observations in the ecliptic. Quasi‐linear time evolutions predicted by the theory are confirmed by the particle‐in‐cell simulations, which also suggest possible explanations for the inherent differences determined by theoretical constraints. These results provide premises for an advanced methodology to characterize, realistically, the electromagnetic electron cyclotron instability and its implication in the solar wind. Key Points: A quasi‐linear approach is formulated for the electromagnetic electron cyclotron (EMEC) instability in conditions typical for the solar wind The core and halo populations involve distinctively in both the linear and quasi‐linear stages of the instability Premises are provided for an advanced methodology to characterize, realistically, the EMEC instability and its implication in the solar wind